Social and Moral Values in Kompas 2022 Selected Short Stories and Its Feasibility as Literature Teaching Materials in High School: Nilai Sosial dan Nilai Moral dalam Cerpen Pilihan Kompas 2022 Serta Kelayakannya Sebagai Bahan Ajar Sastra Di SMA - Adennia Thaffana; Agus Nuryatin (Anthology: Journal of Language, Literature, and Learning, 2025)
The massive influence of science and technology has gradually shifted a person's social and moral values. Without good self-control, the younger generation will fall into detrimental things. Such as the emergence of social deviations due to moral degradation. Instilling social and moral values ​​can help students avoid such behavior in the school environment. Therefore, in integrating the instillation of social and moral values ​​as an effort to deal with social deviations and moral degradation, one of the steps that can be taken is through literary works such as short stories in literature learning. The purpose of this study was to (1) describe the social and moral values ​​contained in the 2022 Kompas Selected Short Stories and (2) see its suitability as literature teaching materials at the high school level. The method used is qualitative descriptive research with a sociology of literature approach. The data collection techniques used are note-taking and documentation techniques. This study focuses on words, phrases, sentences, paragraphs, and dialogues contained in the 2022 Kompas Selected Short Stories that contain social and moral values ​​and are relevant as literature teaching materials in high school. The results of the study show that from the seven short stories analyzed in the 2022 Kompas Selected Short Stories, social values ​​were found in the form of (1) personality, (2) material, (3) biological, (4) legal compliance, (5) knowledge, (6) religion, (7) beauty. Then, the moral values ​​found were the relationship between humans and God, the relationship between humans and themselves, and the relationship between humans and their social environment. In terms of its relevance viewed from the aspects of language, psychology, and cultural background, the Selected Short Stories of Kompas 2022 are appropriate and relevant to be used as alternative teaching materials for literature appreciation in high school at the learning achievement phase F, where students are able to evaluate ideas and perspectives based on logical thinking principles from reading various types of texts (nonfiction and fiction) in print and electronic media. Students are able to appreciate fictional and nonfictional texts. Pengaruh ilmu pengetahuan dan teknologi yang begitu masif telah menggeser nilai-nilai sosial dan moral seseorang secara perlahan. Tanpa adanya pengendalian diri yang baik, generasi muda akan terjerumus pada hal-hal yang merugikan. Seperti munculnya penyimpangan sosial akibat degradasi moral. Penanaman nilai-nilai sosial dan moral dapat membantu siswa terhindar dari perilaku tersebut di lingkungan sekolah. Oleh karena itu, dalam mengintegrasikan penanaman nilai-nilai sosial dan moral sebagai upaya penanganan penyimpangan sosial dan degradasi moral, salah satu langkah yang dapat ditempuh adalah melalui karya sastra seperti cerpen dalam pembelajaran sastra. Tujuan penelitian ini adalah untuk (1) mendeskripsikan nilai-nilai sosial dan moral yang terkandung dalam Cerpen Pilihan Kompas 2022 dan (2) melihat kesesuaiannya sebagai bahan ajar sastra di jenjang SMA. Metode yang digunakan adalah penelitian deskriptif kualitatif dengan pendekatan sosiologi sastra. Teknik pengumpulan data yang digunakan adalah teknik catat dan dokumentasi. Penelitian ini berfokus pada kata, frasa, kalimat, paragraf, dan dialog yang terdapat dalam Cerpen Pilihan Kompas 2022 yang mengandung nilai-nilai sosial dan moral serta relevan sebagai bahan ajar sastra di SMA. Hasil penelitian menunjukkan bahwa dari ketujuh cerpen yang dianalisis dalam Cerpen Pilihan Kompas 2022, ditemukan nilai-nilai sosial berupa (1) kepribadian, (2) kebendaan, (3) biologis, (4) kepatuhan hukum, (5) pengetahuan, (6) agama, (7) keindahan. Kemudian, nilai-nilai moral yang ditemukan berupa hubungan manusia dengan Tuhan, hubungan manusia dengan dirinya sendiri, dan hubungan manusia dengan lingkungan sosialnya. Ditinjau dari relevansinya ditinjau dari aspek bahasa, psikologi, dan latar belakang budaya, Cerpen Pilihan Kompas 2022 layak dan relevan untuk dijadikan bahan ajar alternatif apresiasi sastra di SMA pada fase capaian pembelajaran F, di mana siswa mampu mengevaluasi gagasan dan perspektif berdasarkan kaidah berpikir logis dari membaca berbagai jenis teks (nonfiksi dan fiksi) di media cetak dan elektronik. Siswa mampu mengapresiasi teks fiksi dan nonfiksi.